Memoirs of a Bystander : A Life in Diplomacy - Akhund, Iqbal (Karachi, Pakistan Oxford University Press, 2006)
The skirmish in the Rann of Kutch and the 1965 war with India, the Tashkent Conference, Bhutto's walk-out from the Security Council, Bhutto's rise and fall, and the nuclear deal with France - the author writes of these events as a witness, and tells Pakistan's inside story in this book.
Include Index, Appendix, Epilouge and Illustration
Originally published: Oxford University Press, 1997.
Keywords: Pakistan -- Akhund, Iqbal -- Diplomats